Huzir Sulaiman's Atomic Jaya : a critique of the political and social situation of the nation - Nur Aqwa Jasbi (International Institute of Islamic Thought and Other Civilizations, International Islamic University Malaysia, 2018)
The use of jokes, puns and humour in order to give objective opinions and critiques are some of the best methods in avoiding tenses in communication. This explains the existence of the arts of imitating and making fun of the deficiency of human behaviour and surrounding issues known as satire. The purpose of this study is to establish that Huzir Sulaiman's Atomic Jaya (1998) is a satire based on linguistic evidence found in the text by applying Leech's (1970) diagram of foregrounding realization and Fairclough's (1995) orderliness and naturalization framework. In particular, the aim of this study is to establish the relationship between the political and social satire portrayed in Atomic Jaya to the actual situation in the 1990s and today. Based on the related linguistic evidence, Atomic Jaya is indeed a satire that critiques the issue of national hubris, politically, as well as circulating on racial issues, socially.